2021
DOI: 10.1002/cjoc.202100453
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behaviors of Multi‐tailed B2AB2‐Type Regio‐isomeric Giant Surfactants at the Columnar‐Spherical Boundary

Abstract: Main observation and conclusion We report herein the precision synthesis and phase behaviors of multi‐tailed B2AB2‐type regio‐isomeric giant surfactants consisting of a hydrophilic polyhedral oligomeric silsesquioxane (POSS) head tethered with four hydrophobic polystyrene (PS) tails. The synthesis was accomplished through two sequential “click” reactions to give a series of regio‐isomeric giant surfactants S2DS2 (where S is short for PS tails and D for hydroxyl‐functionalized POSS) in para‐, meta‐, and ortho‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Previously, we have shown that the reaction between octavinyl POSS and 1-thioglycerol gives a mixture of different adducts from which the three bifunctional POSS isomers can be isolated and fully identified. 22 These ortho-, meta-, and para-isomers of bifunctional POSS are ideal scaffolds for regioisomer design. 11 By replacing the soft building blocks in previous examples (e.g., polystyrene chains and noncrystalline POSS) with a crystalline BPOSS, we intended to introduce crystallization as a strong competing force to phase separation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that the reaction between octavinyl POSS and 1-thioglycerol gives a mixture of different adducts from which the three bifunctional POSS isomers can be isolated and fully identified. 22 These ortho-, meta-, and para-isomers of bifunctional POSS are ideal scaffolds for regioisomer design. 11 By replacing the soft building blocks in previous examples (e.g., polystyrene chains and noncrystalline POSS) with a crystalline BPOSS, we intended to introduce crystallization as a strong competing force to phase separation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…straightforward way to prepare such tetrafunctional POSS is via thiol−ene chemistry using thiolglycerol. 22 The bifunctional regioisomers (V 6 T 8 -4OH) were converted to V 6 T 8 -4yne and linked with four BPOSS through a copper-catalyzed alkyne− azide cyclization reaction to give B 2 VB 2 (Scheme 1, see Figures S1 and S2 for 1 H NMR and 13 C NMR characterizations). 24 Then, the vinyl groups were converted to hydroxyl groups to yield the Janus nanograins B 2 DB 2 by a second thiol−ene reaction (see Figures S3 and S4 for NMR characterizations).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the metaand para isomers showed HEX phase and the ortho-isomer formed metastable DQC phase. 152 Recently, porous organic polymers (POPs) have been attracting much attention because they possess high surface areas, low densities, high chemical and thermal stabilities, and tunable porosities; they can be classified into hypercrosslinked polymers, covalent organic frameworks, covalent triazine frameworks, and conjugated microporous polymers. [153][154][155][156][157][158][159][160][161][162][163] These POPs have a diverse range of applications in energy storage, gas capture and separation, photocatalysis, H 2 evolution, and optical devices.…”
Section: Self-assembly Of Di-functionalized Poss Npsmentioning
confidence: 99%
“…For example, the meta - and para isomers showed HEX phase and the ortho -isomer formed metastable DQC phase. 152…”
Section: Introductionmentioning
confidence: 99%